Spatial Resolving Power and Contrast Sensitivity Are Adapted for Ambient Light Conditions in Australian Myrmecia Ants - Ogawa, Yuri; Ryan, Laura A.; Palavalli-Nettimi, Ravindra; Seeger, Olivia; Hart, Nathan S.; Narendra, Ajay (Frontiers in Ecology and Evolution, 2019)
The eyes of most animals exhibit a trade-off between spatial resolving power and absolute sensitivity, which likely reflects functional adaptations for the animals’ visual ecology. When animals operate in dim light conditions, the sensitivity of an eye needs to be increased because the signal-noise ratio of visual information is typically low, even though this potentially compromises spatial resolving power. Here, we investigated the spatial resolving power and contrast sensitivity in two congeneric ant species: the diurnal-crepuscular Myrmecia tarsata and the nocturnal Myrmecia midas using pattern electroretinography (PERG). Both ant species have a specialised zone in the medio-frontal region of the eye that has enlarged facets compared to the rest of the eye. Using the PERG technique, we found that spatial resolving power was 0.60 cycles per degree (cpd) in M. tarsata, while it was 0.57 cpd in M. midas. This variation in spatial resolving power is explained by differences in ommatidial facet diameters, which were significantly larger in the nocturnal M. midas. The contrast sensitivity reached a maximum of 15.5 at 0.1 cpd in M. tarsata and 21.2 at 0.05 cpd in M. midas. The contrast sensitivity functions did not differ significantly between the two species. In the diurnal-crepuscular M. tarsata, the specialised eye region with the largest facets provides both high spatial resolving power and contrast sensitivity making it an ‘acute zone’. In contrast, in the nocturnal M. midas the specialised eye region with the largest facets improves eye’s sensitivity, making it a ‘bright zone’. The increased sensitivity would be important under low luminance conditions and/or for discriminating objects of low contrast. We conclude that even closely related species active at different ambient light intensities have evolved different strategies to optimise their visual system to match their respective visual ecologies.